THE IMPACT OF BIOPHILIC DESIGN ON COGNITIVE ABILITIES IN UNIVERSITY LIBRARY SETTINGS AND URBAN EDUCATIONAL ENVIRONMENTS - MD Sakip, Siti Rasidah; Mohd Khair, Nur Afizah; MD Ajis, Azizah (PLANNING MALAYSIA, 2024)
This study explores the potential of biophilic design to enhance student learning within university libraries, an often-neglected aspect of urban design. While offices and hospitals have been extensively studied for their impact on well-being and performance, post-secondary education settings have received limited attention. A mixed-methods approach was conducted in this study, including interviews, VR simulation experiments, and a questionnaire survey. The results revealed a significant reduction in participants' blood pressure and heart rate following the implementation of the biophilic design. There were also unanimous reports of improved learning experiences; statistical analysis confirmed these positive effects, highlighting the calming influence of biophilic indoor environments on students. The study emphasised the benefits of creating conducive learning spaces and fostering pro-environmental behaviours. This research underscores the importance of integrating sustainable and biophilic design principles into urban educational environments, ultimately enhancing student well-being and academic performance in a student-centric urban design theme.